Study on the Definition of Moulded Bra Cup Features and Parametric Modeling (Journal of Fiber Bioengineering and Informatics, 2018)
In order to make bra cups meet the needs of female customers, as well as to enhance the efficiency ofdesigning bra products, this paper made a study on the definition of digital moulded bra cup mouldingfeatures and parametric modeling by means of parametric features design. The study introduced theconcepts of moulded bra cup's shape features and then defined the same. The instructional effectsof female breast shape features and size features being involved in designing of moulded bra cups wereanalyzed. The relationship between the shape features and size features of breasts and the shape featuresof moulded bra cups were also discussed. Meanwhile, the study made a parametric presentation on thefeature points and feature curves of moulded bra cups. It realized that parametric modeling should aimat feature points and curves. The processes of modeling of digital moulded bra cup were mentioned, andwere made more visualized adhering to human's designing principles, which enhancing the efficiency ofdeveloped moulded bra cup products.
Keywords: Moulded Bra Cup; Shape Features; Parametric; Female Breast Shape